THE INFLUENCE OF STORM MOVEMENT ON WATER EROSION: STORM DIRECTION AND VELOCITY EFFECTS - de Lima J.L.M.P.; Singh V.P.; de Lima M.I.P. (My University, 2003)
Although the problem of storm movement affecting flows (shape of the hydrograph and peak discharges) has been recognised for a long time, most overland flow and water erosion studies do not take into account the effect on the runoff response caused by the movement of the storm across the catchment. Ignoring of the storm movement can result in considerable over- and underestimation of runoff volumes and peaks, and associated soil loss by sheet erosion.This work shows the results of laboratory experiments that were undertaken to study the effect of moving storms on the water erosion process. The experiments were carried out using a soil flume adjustable to different slopes and a movable sprinkling-type rainfall simulator. Both the effects of storm velocity and direction, and surface slope were studied. To simulate moving rainstorms, the rainfall simulator was moved upstream and downstream over the soil surface. The results show that the storm direction and velocity strongly affect the water erosion process. The soil loss caused by the downstream moving rainstorms is higher than that caused by the identical upstream moving rainfall storms.
Keywords: SOIL EROSION; STORM MOVEMENT; RAINFALL SIMULATION; OVERLAND FLOW